2011
DOI: 10.1002/yd.425
|View full text |Cite
|
Sign up to set email alerts
|

Promoting youth purpose: A review of the literature

Abstract: This article reviews the research literature on teaching and supporting purpose in adolescence and young adulthood. An extensive search revealed that most studies on youth purpose examine psychological correlates and neglect instructional and social supports. School is an effective context for fostering purpose, yet reported approaches for explicitly instructing for purpose are rare after the early 1990s, reflecting a trend away from a language of purpose as a discrete endeavor in education since at least the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 15 publications
0
29
0
15
Order By: Relevance
“…Moran et al (2013) found that students high in purpose perceived their teachers as providing opportunities, information, and support, concluding that ''youth with purposes recognized the specific ways that education was integral to their specific [purposeful] aims' ' (p. 19). In their review of the literature of the various ways in which youth purpose can be fostered, Koshy and Mariano (2011) highlighted the emerging evidence that supportive teachers can play critical roles in the development of purpose; however, they also noted that investigations of ''instructional approaches to teach specifically for purpose are absent from academic research journals' ' (p. 16). Indeed, the literature suggests that what is as yet poorly understood is not whether, but how teachers can foster purpose development.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Moran et al (2013) found that students high in purpose perceived their teachers as providing opportunities, information, and support, concluding that ''youth with purposes recognized the specific ways that education was integral to their specific [purposeful] aims' ' (p. 19). In their review of the literature of the various ways in which youth purpose can be fostered, Koshy and Mariano (2011) highlighted the emerging evidence that supportive teachers can play critical roles in the development of purpose; however, they also noted that investigations of ''instructional approaches to teach specifically for purpose are absent from academic research journals' ' (p. 16). Indeed, the literature suggests that what is as yet poorly understood is not whether, but how teachers can foster purpose development.…”
mentioning
confidence: 97%
“…We posit these hypotheses will hold across the samples because there is no directly relevant crosscultural research basis for positing that any particular cultural differences will operate in such a way as to lead to differential relations. In light of Koshy and Mariano's (2011) assessment that there is little to no research that addresses instructional approaches for teaching purpose, alongside the lack of cross-cultural research on the topic, we are taking an exploratory approach to the second research question rather than attempting to offer weakly informed hypotheses.…”
mentioning
confidence: 99%
“…Moran's paper and Quinn's paper examine beliefs among American teachers, providing empirical support for what some educators have suspected: even though purpose is not integrated into the public school curriculum, it is on the radar of American teachers' instruction (e.g. Koshy and Mariano 2011). The paper by Kuusisto, gholami and Tirri finds that the Finnish and Iranian teachers' self ratings of competence were predicted by their higher levels of ethical sensitivity, such as caring about others.…”
Section: Purposeful Teaching Around the Worldmentioning
confidence: 95%
“…Teachers are particularly important for fostering life purpose among pupils (Tirri 2014;Tirri and ubani 2013). Teachers provide encouragement, guidance, opportunities to engage and pathways (Koshy and Mariano 2011;Malin et al 2013;Moran et al 2012). They are role models and instructors for goal-directedness, planfulness (i.e.…”
Section: Purpose In Educational Contextmentioning
confidence: 99%
“…Ela é composta por dois capítulos teóricos e um capítulo teórico-descritivo. O primeiro, intitulado "A construção psicossocial dos projetos de vida" tem o objetivo de apresentar o conceito de projeto de vida ao qual nos filiamos, bem como seu processo de construção, que envolve tanto fatores psíquicos como sociais (DAMON;MENON;BRONK, 2003;DAMON, 2009;BUNDICK, 2009;KOSHY; MARIANO, 2011; entre outros). Em um segundo momento, traçamos um panorama dos estudos desenvolvidos até o momento sob esse marco teórico (BUNDICK, 2011;BROWN;KANNY;PIZZOLATO, 2011;MARIANO et al, 2011;BUNDICK;JOHNSON;YEAGER, 2012;MALIN et al, 2013, entre outros) e apontamos as lacunas por eles deixadas, apresentando em que medida tentaremos superá-las.…”
Section: Introductionunclassified